PENGUATAN BAHASA INGGRIS DASAR KEPADA ANAK DIDIK YAYASAN DHARMA SATYA GRAHA, DESA MEKARJATI, INDRAMAYU - Fariz Sya’ban Hasbulloh; Ardienal Abdillah; Anis Asmarani; Muhammad Rafi Anshari; Fitri Rachmiati Sunarya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This Community Service (PKM) focuses on strengthening basic English literacy at the Dharma Satya Graha Foundation, Mekarjati Village, Indramayu. The background of this activity is the importance of early vocabulary mastery, faced with the main problem of low vocabulary mastery (the initial average is only 8-9 words per student) and the limitations of interactive teaching methods in the partner environment. The main objective of PKM is to introduce daily vocabulary and provide a fun alternative learning method to increase students' interest and basic English language skills. The activity was carried out for three weeks in three meetings, adopting a participatory Action Research approach with 45 subjects from early childhood to junior high school levels. The training method intervention is divided into two main techniques: First, vocabulary training using specially designed flash card media (A5 size, printed in color, with basic themes such as animals, colors, numbers, and body parts). Second, strengthening memory and verbal courage through singing English songs accompanied by movements. Data were analyzed descriptively comparatively (pre-test and post-test). The results demonstrated significant effectiveness of the intervention, with basic vocabulary mastery increasing by an average of 12–14 words per student. Effectively, the singing method also successfully increased children's enthusiasm and self-concept, as measured by an average score increase of 23.3% (from 45% to 68.3%). In conclusion, the combination of edutainment methods (visual and auditory/kinesthetic) is a practical and proven solution to address limitations in learning facilities and motivation.